Indian Hedgehog release from TNF-activated renal epithelia drives local and remote organ fibrosis - O'Sullivan, Eoin D; Mylonas, Katie J; Xin, Cuiyan; Baird, David P; Carvalho, Cyril; Docherty, Marie-Helena; Campbell, Ross; Matchett, Kylie P; Waddell, Scott H; Walker, Alexander D; Gallagher, Kevin M; Jia, Siyang; et al. (Science translational medicine, 2023)
Progressive fibrosis is a feature of aging and chronic tissue injury in multiple organs, including the kidney and heart. Glioma-associated oncogene 1 expressing (Gli1 ) cells are a major source of activated fibroblasts in multiple organs, but the links between injury, inflammation, and Gli1 cell expansion and tissue fibrosis remain incompletely understood. We demonstrated that leukocyte-derived tumor necrosis factor (TNF) promoted Gli1 cell proliferation and cardiorenal fibrosis through induction and release of Indian Hedgehog (IHH) from renal epithelial cells. Using single-cell-resolution transcriptomic analysis, we identified an "inflammatory" proximal tubular epithelial (iPT) population contributing to TNF- and nuclear factor κB (NF-κB)-induced IHH production in vivo. TNF-induced Ubiquitin D ( ) expression was observed in human proximal tubular cells in vitro and during murine and human renal disease and aging. Studies using pharmacological and conditional genetic ablation of TNF-induced IHH signaling revealed that IHH activated canonical Hedgehog signaling in Gli1 cells, which led to their activation, proliferation, and fibrosis within the injured and aging kidney and heart. These changes were inhibited in mice by deletion in -expressing cells or by pharmacological blockade of TNF, NF-κB, or Gli1 signaling. Increased amounts of circulating IHH were associated with loss of renal function and higher rates of cardiovascular disease in patients with chronic kidney disease. Thus, IHH connects leukocyte activation to Gli1 cell expansion and represents a potential target for therapies to inhibit inflammation-induced fibrosis.